Implementasi Deterrence Social sebagai Pencegahan Pelanggaran Lalu Lintas Remaja - Pratama, Muhammad Rizki Aji; Sundawa, Dadang; Muthaqin, Dwi Iman (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Transportation is central to sustainable development, so transportation is included in the Sustainable Development Goals (SDGs) topic. One of the efforts to advance transportation is through law enforcement. As a state of law, Indonesia established Law No. 22/2009 on Road Traffic and Transportation to organize a safe, orderly, and smooth land transportation system. But in reality, many traffic violations still occur in Indonesia, including the Sukabumi City area, where most violators are teenagers. Thus, it is necessary to study the implementation of Law No. 22/2009 on Traffic and Transportation in preventing juvenile traffic violations. This study aims to determine the conditions, situations, and causes of juvenile traffic violations and analyze the application of social deterrence in preventing juvenile traffic violations in Sukabumi City. This research uses a qualitative approach with a normative juridical method. The conditions and situation of youth traffic violations in Sukabumi City are still quite high and the forms of traffic violations that are often violated are not having a driver's license and not wearing a helmet. The occurrence of teenage traffic violations is caused by a lack of awareness of traffic laws, showing identity, laziness, transportation costs, and lack of parental supervision. The application of social deterrence has been well implemented by Satlantas Polres Sukabumi Kota and SMA Negeri 1 Kota Sukabumi. However, the sanctions given are not firm enough, so there is a potential for violators to commit violations again.